2011
DOI: 10.1088/0957-0233/23/1/015401
|View full text |Cite
|
Sign up to set email alerts
|

A novel spatter detection algorithm based on typical cellular neural network operations for laser beam welding processes

Abstract: Real-time monitoring of laser beam welding (LBW) has increasingly gained importance in several manufacturing processes ranging from automobile production to precision mechanics. In the latter, a novel algorithm for the real-time detection of spatters was implemented in a camera based on cellular neural networks. The latter can be connected to the optics of commercially available laser machines leading to real-time monitoring of LBW processes at rates up to 15 kHz. Such high monitoring rates allow the integrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Simulation results were compared to those of a reference file which was built through visual inspection of the process images. Analyses of the detection rate of spatters and FPH were largely discussed in [14,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results were compared to those of a reference file which was built through visual inspection of the process images. Analyses of the detection rate of spatters and FPH were largely discussed in [14,15].…”
Section: Resultsmentioning
confidence: 99%
“…The proposed closed-loop control system leads to the on-line adjustment of the laser power with controlling rates of up to 14 kHz. Furthermore, in [14] we showed that the occurrence of spatters can also be observed in LBW in order to provide quality information about the process at monitoring rates of 15 kHz.…”
Section: Introductionmentioning
confidence: 98%
“…In this study, the molten pool around the keyhole was selected as the ROI (Region of Interesting, its resolution is 256 pixels and 211pixels) as it is the region which was the most violently varied part of molten pool, the cropped image is shown in Fig.5(a).The result of enhancement of Fig.5(a) with the piecewise linear stretching histogram equalization method is shown in Fig.5 The enhanced image shown in Fig.5 A c c e p t e d M a n u s c r i p t 11 areas, which were produced by spatters, also existed, and it will interfere the morphology information of molten pool. Through the experimental statistics, the area of these noisy regions was less than 200 pixels.…”
Section: (A)mentioning
confidence: 99%
“…The molten pool formed due to integrated forces of the vapor pressure of liquid metal caused by high power laser beam, the surface tension of molten pool, the blowing force of shielding gas and the fluid gravity in the keyhole [11][12][13], and its morphology varied violently. Yamada et al carried out X-ray imaging of inside materials to observe behavior of molten pool using intense synchrotron radiation during laser welding [14], but the X-ray imaging system were expensive and harmful to operators.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 25 years cellular nonlinear networks (CNN) [10] have proved to be suitable for high-speed image processing in numerous fields of application [6,27,28,38]. The concept of the CNN universal machine (CNN-UM) [31] evolves these networks to freely programmable and universal processors which-in contrast to numerous specialised image processing machines-are not limited to certain operations, but offer a broad selection of image processing operators and algorithms [18].…”
Section: Introductionmentioning
confidence: 99%